PENGARUH KOMITMEN ORGANISASI DAN KETERAMPILAN MANAJERIAL TERHADAP KINERJA KEPALA SEKOLAH DASAR DI KECAMATAN GUNEM KABUPATEN REMBANG - Agus Suwarno; Noor Miyono; Widya Kusumaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The performance of the school principal is one of the factors that becomes a benchmark for school success. The principal's performance in question is awareness of the need to implement the rules determined by the school. Having good organizational commitment will enable a teacher to benefit himself and the school. The objectives of this research are (1) to determine the influence of organizational commitment on the performance of school principals (2) to determine the influence of managerial skills on the performance of school principals (3) to determine the influence of organizational commitment and managerial skills together on the performance of state elementary school principals in Gunem District, Regency Rembang..The population of this study were teachers at 20 elementary schools in Gunem District, Rembang Regency, totaling 116 people, a sample of 90 teachers selected using proportional random sampling technique at each school. Validity, reliability and descriptive data analysis tests, single regression and multiple regression tests using the SPSS for Windows version 23 program. Research findings: (1) organizational commitment has a positive influence on principal performance of 38.5% with the regression equation Ŷ= 61.958 + 0.225X1, (2) managerial skills have a positive influence on principal performance of 60.6% with the regression equation Ŷ = 41.444 + 0.276X2, (3) organizational commitment and managerial skills together on the performance of school principals which is 62.4% with the regression equation Ŷ = 56.587 + 0.433X1 + 0.350X2, Based on the findings above: (1) the principal intensifies the evaluation of school performance results, (2) the principal increases supervision in the main work duties of teachers, (3) teachers increase involvement in school activities.